2017
DOI: 10.1155/2017/3510796
|View full text |Cite
|
Sign up to set email alerts
|

Source and Ecological Risk Characteristics of PAHs in Sediments from Qinhuai River and Xuanwu Lake, Nanjing, China

Abstract: In order to investigate the residual characteristics, sources, and ecological risk of PAHs in sediment from urban rivers, the sediments of 15 typical sites from Qinhuai River and Xuanwu Lake, which are typical urban rivers and lake, were collected from October 2015 to July 2016; the sources of PAHs in sediment were also identified by several methods. Results showed that ∑PAHs concentration in sediment ranged from 796.2 ng/g to 10,470 ng/g with an average of 2,713.8 ng/g. High molecular weight PAHs with 4-5 rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 88 publications
(105 reference statements)
1
20
0
Order By: Relevance
“…Table 3 shows values > 0.35 for both water and sediment, implying contributions from the burning of nonpetroleum materials, such as refuse or biomass as another major pyrolytic input. This assertion was confirmed in the sediment samples with the use of BaA/228 (Jiao et al 2012 ; Zhao et al 2017 ).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Table 3 shows values > 0.35 for both water and sediment, implying contributions from the burning of nonpetroleum materials, such as refuse or biomass as another major pyrolytic input. This assertion was confirmed in the sediment samples with the use of BaA/228 (Jiao et al 2012 ; Zhao et al 2017 ).…”
Section: Resultsmentioning
confidence: 81%
“…2 . The fairly low level of ∑PAH recorded at E4 may be ascribed to the possible tidal flushing of contaminants adsorbed on sediment particle close to the mouth of the estuary where it discharges into the Indian Ocean (Zhao et al 2017 ). Average levels at the four sampling points were all above the ERL and below effect range median (ERM; 44,792 µg/kg dw).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above observation did not agree with those of [21]. That observed values lower than 0.1 in the ratio between An/(An+Phe) in sediments from Yinma River, China, but agrees with those of sediment from Pearl River, China and those of sediments Qinhuai River and Xuanwu Lake, Nanjing, China, where there was excessive coal and grass burning along the area [29,30].…”
Section: Source Diagnosis Of Pahsmentioning
confidence: 59%
“…Interestingly, fluoranthene and anthracene were not detected in the present study possibly because they were below the detection limit of the GCMS instrument used. More recently, an investigation of the residual characteristics, sources and ecological risks of PAHs in sediment from 15 typical sites from Qinhuai River and Xuanwu Lake typical urban rivers and lakes collected from October 2015 to July 2016 showed that ∑ PAHs concentration in sediment ranged from 796.2 to 10,470 ng g −1 with an average of 2713.8 ng g −1 [5]. However, the concentrations reported in this study are significantly higher than most of the PAH levels reported elsewhere, suggesting a direct source of PAH precursors into River Elburgon.…”
Section: Introductionmentioning
confidence: 99%